Global Market Power and its Macroeconomic Implications - Diez, Federico (IMF Working Papers; Working Paper ;, 2018)
We estimate the evolution of markups of publicly traded firms in 74 economies from 1980-2016. In advanced economies, markups have increased by an average of 39 percent since 1980. The increase is broad-based across industries and countries, and driven by the highest markup firms in each economic sector. For emerging markets and developing economies, there is less evidence of a rise in markups. We find a positive relation between firm markups and other indicators of market power, such as profits or industry concentration. Focusing on advanced economies, we investigate the relation between markups and investment, innovation, and the labor share at the firm level. We find evidence of a non-monotonic relation, with higher markups being correlated initially with increasing and then with decreasing investment and innovation rates. This non-monotonicity is more pronounced for firms that are closer to the technological frontier. More concentrated industries also feature a more negative relation between markups and investment and innovation. The association between markups and the labor share is generally negative.